The Three Ds of Transcription Activation by Glucagon: Direct, Delayed, and Dynamic - Goldstein, Ido (Endocrinology, 2017)
Upon lowered blood glucose occurring during fasting, glucagon is secreted from pancreatic islets, exerting various metabolic effects to normalize glucose levels. A considerable portion of these effects is mediated by glucagon-activated transcription factors (TFs) in liver. Glucagon directly activates several TFs via immediate cyclic adenosine monophosphate (cAMP)– and calcium-dependent signaling events. Among these TFs, cAMP response element-binding protein (CREB) is a major factor. CREB recruits histone-modifying enzymes and cooperates with other TFs on the chromatin template to increase the rate of gene transcription. In addition to direct signal transduction, the transcriptional effects of glucagon are also influenced by dynamic TF cross talk. Specifically, assisted loading of one TF by a companion TF leads to increased binding and activity. Lastly, transcriptional regulation by glucagon is also exerted by TF cascades by which a primary TF induces the gene expression of secondary TFs that bring about their activity a few hours after the initial glucagon signal. This mechanism of a delayed response may be instrumental in establishing the temporal organization of the fasting response by which distinct metabolic events separate early from prolonged fasting. In this mini-review, we summarize recent advances and critical discoveries in glucagon-dependent gene regulation with a focus on direct TF activation, dynamic TF cross talk, and TF cascades.